Computerized Generation and Finite Element Stress Analysis of Endodontic Rotary Files - Roda Casanova, Victor; Zubizarreta Macho, Álvaro; Sánchez Marín, Francisco; Alonso Ezpeleta, Óscar; Albaladejo Martínez, Alberto; Galparsoro Catalán, Agustín (My University, 2021)
Introduction: The finite element method has been extensively used to analyze the mechanical behavior of endodontic rotary files under bending and torsional conditions. This methodology requires elevated computer-aided design skills to reproduce the geometry of the endodontic file, and also mathematical knowledge to perform the finite element analysis. In this study, an automated procedure is proposed for the computerized generation and finite element analysis of endodontic rotary files under bending and torsional conditions. Methods: An endodontic rotary file with a 25 mm total length, 0.25 mm at the tip, 1.20 mm at 16 mm from the tip, 2 mm pitch and squared cross section was generated using the proposed procedure and submitted for analysis under bending and torsional conditions by clamping the last 3 mm of the endodontic rotary file and applying a transverse load of 0.1 N and a torsional moment of 0.3 N · cm. Results: The results of the finite element analyses showed a maximum von Mises stress of 398 MPa resulting from the bending analysis and a maximum von Mises stress of 843 MPa resulting from the torsional analysis, both of which are next to the encastre point. Conclusions: The automated procedure allows an accurate description of the geometry of the endodontic file to be obtained based on its design parameters as well as a finite element model of the endodontic file from the previously generated geometry. Keywords: endodontic file; bending; torsion; stress distribution; finite element analysis